The Impact of Patient Hygiene on Skin Issues in Lower Limb Prosthesis Users - Nur Rachmat; Sisybania; Maharani Nadia Andarini (Poltekkes Kemenkes Surabaya, 2025)
Amputees require effective support through prostheses, which help restore mobility. Maintaining cleanliness of the stump and prosthesis is essential to prevent skin problems, ensuring comfort during activities. This study aims to determine the relationship between patients' cleanliness levels and skin issues on the stumps of lower limb prosthesis users. This research was conducted in December 2023 at the Community Resource Rehabilitation Development and Training Center (PPRBM) Solo, utilizing the Self-Management Assessment for the Residuum and Prosthesis (S.M.A.R.T) in a cross-sectional observational design. A purposive sampling technique was used to select 40 lower limb prosthesis users. Data analysis involved the Shapiro Wilk normality test and hypothesis testing with Pearson Product Moment. Analysis of the 40 participants revealed a significance value of p = 0.000 (p < 0.05) and a correlation coefficient of -0.737. This indicates a significant and strong negative correlation: higher cleanliness levels correspond to fewer skin problems on the stump, while lower cleanliness levels lead to more skin issues. Maintaining a high level of cleanliness is crucial for lower limb prosthesis users to prevent skin issues on the stump.